Investigating the scaling of masonry structures in a blast environment. (15th December 2019) - Johns, Robert V.; Clubley, Simon K.
Highlights: New scaling methodology developed for masonry structures subject to blast. Scaling method utilises dynamic similitude to model damage state and rubble. Scaling method found to closely model damage and rubble at range of overpressures. Presents opportunity for blast trials to be conducted in smaller areas with lower cost. Abstract: Full-scale experimental testing of masonry response to blast can be challenging with the requisite need for significant measurement area in conjunction with high construction and material costs. This paper investigates the use of dynamic similitude to produce reduced-scale masonry structures which model the damage state and debris distribution of a full-scale counterpart due to blast loading. An investigation into the fundamental physical components of masonry response to blast loading facilitated the development of a new scaling methodology which maintains the ratio of lateral and vertical force components as prescribed by dynamic similitude. It is shown that this can be accomplished by using a reciprocal scale factor for the reduced-scale structure's density. Computational models of full and reduced-scale masonry response to blast loading were produced with the Applied Element Method (AEM) to verify the underlying theory of the proposed scaling methodology. These utilised single-storey cuboid structures with non-responding roofs and half-thickness stretcher bond construction. Computational Fluid Dynamics (CFD) models of blast wave interaction with the masonry structures were defined at a range of peak overpressures, enabling a remap procedure into AEM. Importantly, AEM models utilised a constant 1:2 scale factor with masonry material parameters for commercially available units, demonstrating the practical applications of this scaling methodology for blast trials. Analysis of the AEM models demonstrated close qualitative agreement in damage state for full and reduced-scale structures at 55 kPa and 110 kPa peak free-field overpressure. These results also indicated agreement for a range of failure modes with the 110 kPa model showing front-panel collapse versus the 55 kPa model which indicated partial front-panel deflection. Chi-square analysis of the resultant debris distribution at 110 kPa indicated quantitative agreement for the relative quantities of bricks found within the rubble pile as a function of their original panel wall location.